Can higher bonuses lead to less effort? Incentive reversal in teams - Esteban F. Klor; Sebastian Kube; Eyal Winter; Ro'i Zultan (Institute for the Study of Labor (IZA), 2011)
Conventional wisdom suggests that an increase in monetary incentives should induce agents to exert higher effort. In this paper, however, we demonstrate that this may not hold in team settings. In the context of sequential team production with positive externalities between agents, incentive reversal might occur: an increase in monetary incentives (either because rewards increase or effort costs decrease) may lead agents to exert lower effort in the completion of a joint task - even if agents are fully rational, self-centered money maximizers. Herein we discuss this seemingly paradoxical phenomenon and report on two experiments that provide supportive evidence.
urn:nbn:de:101:1-201104113740
Keywords: C92; D23; J31; J33; J41; M12; M52; 330; incentives; incentive reversal; team production; externalities; laboratory experiments; personnel economics; Arbeitsgruppe; Leistungsmotivation; Leistungsentgelt; Ökonomischer Anreiz; Arbeitsleistung; Test